SARS-CoV-2 Infection-Induced Promoter Hypomethylation as an Epigenetic Modulator of Heat Shock Protein A1L (HSPA1L) Gene - Muhammad, Jibran Sualeh; Saheb Sharif-Askari, Narjes; Cui, Zheng-Guo; Hamad, Mawieh; Halwani, Rabih (Frontiers in Genetics, 2021)
Numerous researches have focused on the genetic variations affecting SARS-CoV-2 infection, whereas the epigenetic effects are inadequately described. In this report, for the first time, we have identified SARS-CoV-2 induced DNA methylation changes in genes that may regulate COVID-19 infection. In silico transcriptomic data of COVID-19 lung autopsies were used to identify the top differentially expressed genes containing CpG Islands in their promoter region. Similar gene regulations were also observed in an in vitro model of SARS-CoV-2 infected lung epithelial cells (NHBE and A549). The epigenetic regulation of the candidate genes was confirmed in AZA treated NHBE cells, A549 epithelial cells, as well as in U937 immune cells. Moreover, SARS-CoV-2 infection significantly decreased the levels of DNA methyltransferases (DNMT1, DNMT3A, and DNMT3B). Out of 14 epigenetically regulated genes, 12 were upregulated suggesting promoter hypomethylation, while only 2 genes were downregulated. Among those 12 induced genes, HSPA1L and ULBP2 were found to be upregulated upon AZA treatment in both lung epithelial cells as well as immune cells, suggesting their epigenetic regulation. To confirm the hypomethylation of these two genes during SARS-CoV-2 infection, their promoter methylation levels was determined in the genomic DNA obtained from whole blood samples of asymptomatic, severe COVID-19 patients and equally matched healthy controls. The methylation level of HSPA1L was significantly decreased in both asymptomatic and severe COVID-19 blood samples confirming its epigenetic regulation by SARS-CoV-2 infection. SARS-CoV-2 epigenetic regulation of HSPA1L may facilitate viral replication and could be used as a potential target for antiviral treatment.